Faktor-Faktor Yang Mempengaruhi Kecemasan Pasien Pra Operasi Sectio Caesarea - Fatrida, Dedi; Tanjung, Arif Irpan (JURNAL KESEHATAN TERAPAN, 2023)
The purpose of this study was to determine the factors associated with the Anxiety of Preoperative Sectio Caesarea Patients at the Port Hospital of Palembang. The research design used descriptive analytic method with cross sectional approach, and accidental sampling. The population in this study were patients who were about to give birth by Sectio Caesarea at the Port Hospital of Palembang totaling 40 respondents. The sampling technique used is accidental sampling, the number of samples in this study was 40 respondents, data collection in this study used primary data with interviews and questionnaire sheets. From the univariate analysis, it is known that the distribution of respondents who experienced severe category anxiety amounted to 24 respondents (60.0%) which was greater than those who experienced mild category anxiety, which amounted to 16 respondents (40.0%). From the results of bivariate analysis, it was found that there was a significant relationship between knowledge and Anxiety of Preoperative Sectio Caesarea Patients where the value of = 0.000 (ρ-value < 0.05), there was a significant relationship between family support and Anxiety of Preoperative Sectio Caesarea Patients where the value of = 0.000 (ρ-value < 0.05), a significant relationship between counseling from health workers and the Anxiety of Preoperative Sectio Caesarea patients where the value of = 0.000 (ρ-value <0.05) so it can be concluded that there is a significant relationship between knowledge,